2008
DOI: 10.1142/s0219633608004192
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Glycine Conformers

Abstract: Glycine conformers were investigated with three density functional theory (DFT) methods (B3LYP, PBE1PBE, X3LYP), and the second order Moller-Plesset perturbation theory (MP2) combined with basis sets of 6-31+ G*, aug-cc-pVDZ, and aug-cc-pVTZ. Solvation effects were considered by using polarizable continuum model. Results from B3LYP and X3LYP were in generally good agreement with those of MP2, while PBE1PBE was shown to be inferior for the description of conformational potential energy surfaces. Conformers Ip, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
42
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 40 publications
6
42
0
1
Order By: Relevance
“…Therefore the theoretical studies of glycine in aqueous solution have been mainly carried out by three different approaches; (i) calculations of the solute surrounded by some discrete water molecules [10][11][12][13][14][15][16][17][18][19][20][21] (ii) calculations by statistical approaches such as Monte Carlo (MC) 25 or molecular dynamics (MD), 14,19,[22][23][24] and (iii) calculations by use of a dielectric continuum methodology. [26][27][28][29][30][31][32][33] Nevertheless, the experimental findings 1-9 could not be successfully reproduced by most of these approaches, although some qualitative characteristics were consistent with the experimental findings. 2,5 For example, it has been shown that the ZW of glycine exists as an energy minimum when at least two water molecules are included.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Therefore the theoretical studies of glycine in aqueous solution have been mainly carried out by three different approaches; (i) calculations of the solute surrounded by some discrete water molecules [10][11][12][13][14][15][16][17][18][19][20][21] (ii) calculations by statistical approaches such as Monte Carlo (MC) 25 or molecular dynamics (MD), 14,19,[22][23][24] and (iii) calculations by use of a dielectric continuum methodology. [26][27][28][29][30][31][32][33] Nevertheless, the experimental findings 1-9 could not be successfully reproduced by most of these approaches, although some qualitative characteristics were consistent with the experimental findings. 2,5 For example, it has been shown that the ZW of glycine exists as an energy minimum when at least two water molecules are included.…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8][9] High-level ab initio studies demonstrated that the neutral form (NE) of glycine exists in the gas phase but the zwitterionic form (ZW) is unstable in vacuo. [11][12][13][14][15][16][17][18][19][20]27,[30][31][32][33] However, as is well known, the ZW of glycine predominates in crystalline or in aqueous solution, 2 and hence the solvent (or environmental) effects should be included in the theoretical studies to explore the glycine chemistry correctly. Therefore the theoretical studies of glycine in aqueous solution have been mainly carried out by three different approaches; (i) calculations of the solute surrounded by some discrete water molecules [10][11][12][13][14][15][16][17][18][19][20][21] (ii) calculations by statistical approaches such as Monte Carlo (MC) 25 or molecular dynamics (MD), 14,19,[22][23][24] and (iii) calculations by use of a dielectric continuum methodology.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations